Relationship between Chronic Tonsillitis and Vascular Endothelial Growth Factor, Hypoxia, Biofilm and The Development of Therapies for Tonsillitis: Literature Review - Febrian, Rizky; Ristyana, Sabira Husna; Adji, Iwan Setiawan (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Tonsillitis is an inflammatory process that occurs in the palatine tonsils and can affect all ages, especially children. Chronic tonsillitis is a disease that is still a major health problem in the world. This disease can spread and cause percontinuitatum, hematogenous or lymphogenous complications. To date, tonsillectomy is the best option for tonsillitis management, but it is not the safest option because of the postoperative complications that can occur. With the advancement of health science, there are several studies have tried to find medicamentous treatments based pathogenetically against vascular endothelial growth factor, hypoxia and biofilms in tonsilitis that could be new modalities other than surgical therapy such as tonsillectomy. This scientific paper aims to determine the relationship between chronic tonsillitis and vascular endothelial growth factor, hypoxia and biofilm in the pathogenesis of tonsillitis and the development of medical therapy for chronic tonsillitis. Results: Microbial biofilms can lead of recurrent tonsillitis in population pediatric and adult. Using antibiofilm therapis can improve the efficacy of antimicrobials therapy and reduce the dose of systemically administered drugs. Elevated VEGF expression in the tonsil organ can be involved in the pathogenesis of recurrent or chronic tonsillitis. Anti-VEGF may be a potential treatment for tonsillitis by suppressing VEGF expression., in a hypoxia state may worsen the overall inflammatory status. Value: Our results show that there are several new modalities in the treatment of tonsillitis in the form of antibiofilms, and anti-VEGF.